Daya Saing PT Sinar Mas Agri Resources and Technologi (SMART) Tbk sebagai Produsen Minyak Kelapa Sawit - Vandrias Dewantoro; Budi Widayanto; Nurul Nurul (Jurnal Dinamika Sosial Ekonomi, 2009)
Purposes of this research are analyze productivity reached by PT SMART tbk among his competitor and analyze level of efficiency PT SMART Tbk compared to his competitor Method of this research using casual comparability. This research compares between PT SMART Tbk and competitor that is PT PP LONSUM Tbk. PT AALI Tbk and PT. BSP Thk from the size productivity and efficiency, to analyse its competitiveness Result of this research show that company has highest productivity is PT SMARTTbk then second PT PP LONSUM, then PT BSP Thk and lone is PT AALI Thk. then for efficiency, company that is most efficient is produce of CPO is PT SMART Tbk, then secon is PT AALI Tbk, then PT. BSP Tbk and low is PT PP LONSUM Tbk. Conclusion from this research is PT SMART Tbk is company having highest competitiveness because PT SMART Thk has not only the highest productivity but also the highest efficiency Suggestion for PT SMART Tbk are adding machine amount, maintaining management of observation plantation and efficiency cost production up to yielding CPO.Keyword: Competitiveness, Productivity and Efficiency